The Association between Maternal Mortality and Non-Medical factors in African Countries - Lalthapersad-Pillay, P. (Journal of Economics and Behavioral Studies, 2014)
The medical expertise to treat to complications arising from pregnancy and childbirth has not spared girls and women in developing countries from dying of such conditions. Developing countries account for the bulk of the global share of maternal deaths with complications of pregnancy and childbirth being the leading cause of death in young women aged between 15 and 49. Sub-Saharan Africa is responsible for nearly three-fifths of all global maternal deaths which have saddled it with notoriously high levels of maternal mortality ratios, a concern that has been red-flagged internationally and regionally. Most studies on maternal mortality in Africa have been confined to an examination of factors impinging on maternal mortality from both medical and socioeconomic standpoints for individual country’s based on survey data. Our study differs from others as it employs logistic regression to look at the association between non-medical factors and maternal mortality nationally for all African countries. Whilst the results from the logistic regression suggests that there is no statistically significant relationship between any of the variables and maternal mortality, the odds ratio for Human Development Index (HDI) and Gross National Income per capita (GNI) imply that African countries with low HDI are about three time more likely to have high maternal mortality compared to high HDI countries. Similarly, African countries with low GNI are about five times more likely to have high maternal mortality compared to high GNI countries.